ANALISIS EFEKTIVITAS PEMUNGUTAN PAJAK RESTORAN PADA DINS PENDAPATAN PENGELOLA KEUANGAN DAN KEKAYAAN DAERAH KABUPATEN TOBA SAMOSIR - Jenni Nova Yanti Siburian; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Tax is one of the main income sources for a country that is paid by the public. Restaurant tax is a mandatory fee charged to entities or persons for services selling food and / or beverages consumed by the purchaser either in the ministry or in another place with free of charge. Effectiveness research restaurant tax collection was conducted in Toba Samosir. The purpose of this study is to determine and analyze the effectiveness of Tax Collection Restaurant and to identify and analyze factors that influence the effectiveness of the Restaurant Tax Collection Revenue Service Financial Management and Wealth Toba Samosir regency. Based on the results of the Restaurant Tax Collection Effectiveness Analysis at the Department of Revenue Financial Management and Wealth Toba Samosir concluded " yet equally effective " because it is not in accordance with the Regional Regulation Number 1 of 2012 on Local Taxes. Internal factors that cause lack of firmness or legal sanction given to taxpayers who do not obey the restaurant to pay taxes and the lack of socialization of the importance of tax made by the Department of Revenue Financial Management and Wealth Toba Samosir regency. While external factors,namely the lack of knowledge of the importance of tax payers taxes and lack of enthusiasm taxpayer in terms of tax payments. Suggestions for future improvement evaluation is Party Revenue Service Financial Management and Wealth Toba Samosir regency should the restaurant tax purposes in accordance with the Toba Samosir Regency Regulation Number 1 of 2012 on Local Taxes, strict application of sanctions to the taxpayer is delinquent payment of taxes and do education and socialization abiding tax intensively Toba Samosir to the public to raise awareness in terms of tax payments.Keywords : Effectiveness , Tax Withholding and Restaurant